2006
DOI: 10.1136/gut.2005.087668
|View full text |Cite
|
Sign up to set email alerts
|

Acid and non-acid reflux in patients with persistent symptoms despite acid suppressive therapy: a multicentre study using combined ambulatory impedance-pH monitoring

Abstract: Background and aims: Empiric proton pump inhibitor (PPI) trials have become increasingly popular leading to gastroenterologists frequently evaluating gastro-oesophageal reflux disease (GORD) patients only after they have ''failed'' PPI therapy. Combined multichannel intraluminal impedance and pH (MIIpH) monitoring has the ability to detect gastro-oesophageal reflux (GOR) episodes independent of their pH and evaluate the relationship between symptoms and all types of GOR. Using this technique, we aimed to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
413
2
25

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(460 citation statements)
references
References 19 publications
20
413
2
25
Order By: Relevance
“…This technology shed new light in investigation of patients with persistent symptoms despite adequate esophageal acid exposure control by proton pump inhibitors (PPI) (5) . In this regard, MII-pH monitoring has improved the diagnostic yield of GERD patients as it provides better identification of patients with functional heartburn.…”
mentioning
confidence: 99%
“…This technology shed new light in investigation of patients with persistent symptoms despite adequate esophageal acid exposure control by proton pump inhibitors (PPI) (5) . In this regard, MII-pH monitoring has improved the diagnostic yield of GERD patients as it provides better identification of patients with functional heartburn.…”
mentioning
confidence: 99%
“…While 40% of symptoms were related to non-acid reflux, only 10% of symptoms were related to acid reflux. 12 Vela et al 11 suggested that, on omeprazole, the percentage of acid reflux decreased from 45% to 3% but that of non-acid reflux increased from 55% to 97%. 11 Though PPIs are highly effective in neutralizing gastric acid and preventing esophageal acidification, non-acidic liquid reflux remains to be a significant problem in a large proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies that investigated non-acidic reflux in patients who were non-responsive to PPI therapy. [23][24][25] Mainie et al 12 performed impedance pH monitoring in 168 PPI non-responsive GERD patients while on twice daily PPI. While 40% of symptoms were related to non-acid reflux, only 10% of symptoms were related to acid reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Większość Grażyna Jurkowska, Agnieszka Świdnicka-Siergiejko, Andrzej Dąbrowski chorych nieodpowiadających na leczenie stanowią pacjenci z nienadżerkową postacią choroby refluksowej (non-erosive reflux disease -NERD) i zgagą czynnościo-wą. Dzięki zastosowaniu 24-godzinnego pomiaru pH i impedancji wewnątrzprzełykowej wykazano, że w grupie chorych z objawami refluksowymi, utrzymującymi się pomimo leczenia PPI w dawce standardowej stosowanej 2 razy dziennie, 50-60% osób ma objawy niezwiązane z refluksem, 10% ma objawy związane z refluksem kwaśnym, a 30-40% z refluksem niekwaś -nym [4]. Choć PPI są podstawą leczenia GERD, wyniki tych badań sugerują, że potrzebne są nowe metody.…”
Section: Wstępunclassified